Physiology and pathophysiology of the calcium store in the endoplasmic reticulum of neurones - Verkhratsky, Alexei (Henry Stewart Talks, 2007)
Endoplasmic reticulum, Calcium signaling, Intracellular integration, Calcium waves, Calcium signal propagation, Calcium tunnels, Neuronal signaling, Intracellular calcium release channels, Ryanodine receptors (RyR), Inositol (1,4,5) trisphosphate receptors (InsP3Rs), Endoplasmic reticulum stress, Neurodegenerative diseases, Neuronal cell death
Archived at 2020/08/13